Discriminant features of young male handball players - Rudney Uezu; Fernando Oliveira Fernando Paes; Maria Tereza Silveira Böhme; Marcelo Massa (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n4p330   The aim of this study was to assess which variables, in isolation or in combination, differentiate between young handball players at two different competitive levels. The sample was composed of 48 male athletes aged between 13 and 14 years old, 18 of whom played at school level and 30 of whom were league players. Anthropometric measurements, physical fitness and level of tactical knowledge were all evaluated. Data were analyzed using descriptive statistics and logistic regression (backward), with competitive level as the dependent variable and tactical knowledge and kinanthropometric parameters as the independent variables. A combination of height, vertical jump, agility and throwing strength achieved an 88.6% rate of correct classification of the individuals tested. Taken in isolation, height was the variable that best differentiated between the groups, but it is believed that it is necessary to combine this with physical fitness variables.